2010
DOI: 10.1093/jnci/djp458
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 in Melanoma Progression and Metastasis

Abstract: Metastases are responsible for cancer deaths, but the molecular alterations leading to tumor progression are unclear. Overexpression of the E2F1 transcription factor is common in high-grade tumors that are associated with poor patient survival. To investigate the association of enhanced E2F1 activity with aggressive phenotype, we performed a gene-specific silencing approach in a metastatic melanoma model. Knockdown of endogenous E2F1 via E2F1 small hairpin RNA (shRNA) expression increased E-cadherin expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
115
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 45 publications
10
115
0
2
Order By: Relevance
“…From this perspective, aberrantly elevated E2F1 levels in high-grade tumors can be considered as a marker for unfavorable patient survival prognosis. In support of these findings, we have recently shown that dysregulated E2F1 causes malignant progression in therapy-resistant metastatic melanoma xenografts in which depletion of endogenously high E2F1 levels abrogates tumor invasion and pulmonary metastasis (10). According to our results, the aggressive behavior of E2F1 in melanoma cells is partially mediated through the induction of the EGF receptor (EGFR) pathway.…”
Section: Quick Guide To Main Model Equations and Assumptionssupporting
confidence: 85%
“…From this perspective, aberrantly elevated E2F1 levels in high-grade tumors can be considered as a marker for unfavorable patient survival prognosis. In support of these findings, we have recently shown that dysregulated E2F1 causes malignant progression in therapy-resistant metastatic melanoma xenografts in which depletion of endogenously high E2F1 levels abrogates tumor invasion and pulmonary metastasis (10). According to our results, the aggressive behavior of E2F1 in melanoma cells is partially mediated through the induction of the EGF receptor (EGFR) pathway.…”
Section: Quick Guide To Main Model Equations and Assumptionssupporting
confidence: 85%
“…E2F1 plays an important role in regulating development, differentiation, proliferation, cellular signal transduction, and apoptosis (9)(10)(11)(12). Certain studies reported that E2F1 disrupts a range of pathways in numerous cancers and is closely correlated with clinical parameters (13)(14)(15). We had also previously identified that E2F1 is upregulated in ccRCC progression (16).…”
Section: Introductionmentioning
confidence: 89%
“…Our recent in vivo data provide the first functional evidence that E2F1 is crucial in transformed cells for local invasion and to form distant metastases (10). This study showed that knockdown of endogenous E2F1 in a metastatic melanoma model severely reduces the migratory and invasive potential of skin cancer cells, whereas cell proliferation is not affected.…”
Section: Switching Duties: a Tumor Suppressor Contributes To Cancer Pmentioning
confidence: 60%
“…Now the question arises of how E2F1 accomplishes tumor progression and whether this represents a more general paradigm beyond cell-cycle regulation. In malignant melanoma, E2F1-dependent progression was found to be mediated through the upregulation of EGFR and activation of the cytoplasmic Ras/mitogen-activated protein kinase (MAPK)/ extracellular signal-regulated kinase (ERK) and PI3K/AKT signaling cascades, as well as B-Myb transactivation in vitro (10). It seems that the EGFR ligand HBEGF is also a transcriptional target of E2F1, providing the possibility for autocrine stimulation of EGFR signaling in aggressive skin cancer.…”
Section: Switching Duties: a Tumor Suppressor Contributes To Cancer Pmentioning
confidence: 99%